Nature of gold mineralization at Mule Canyon, Lander County, Nevada, USA - T. J. Serenko (The Institute of Materials, Minerals and Mining, 1995)
The epithermal deposit is hosted by Tertiary volcanic rocks that lie between mid-Miocene normal faults of the Northern Nevada Rift. Petrographic, laser-ablation and metallurgical observations suggested that the gold occurs in two principal forms: native (and electrum) and disseminated in arsenopyrite. It was proposed that gold is distributed between two parageneses with distinct mineralogical associations. Detailed downhole geochemical study supported the observations. Concentrations of Au, Ag, As, Sb and Se were determined from drill core and reverse-circulation cutting composites and contoured on cross-sections. Gold was indeed shown to have a bimodal distribution with the two parts separated spatially and perhaps temporally, implying that two separate genetic processes acted to concentrate gold at Mule Canyon